Sport 2.0 transforming sports for a digital world - Miah, Andy 1975- (The MIT Press, 2017)
Ramifications of the convergence of sports and digital technology, from athlete and spectator experience to the role of media innovation at the Olympics. Digital technology is changing everything about modern sports. Athletes and coaches rely on digital data to monitor and enhance performance. Officials use tracking systems to augment their judgment in what is an increasingly superhuman field of play. Spectators tune in to live sports through social media, or even through virtual reality. Audiences now act as citizen journalists whose collective shared data expands the places in which we consume sports news. In Sport 2.0, Andy Miah examines the convergence of sports and digital cultures, examining not only how it affects our participation in sport but also how it changes our experience of life online. This convergence redefines how we think of about our bodies, the social function of sports, and the kinds of people who are playing. Miah describes a world in which the rise of competitive computer game playing-e-sports-challenges and invigorates the social mandate. Miah also looks at the Olympic Games as an exemplar of digital innovation in sports, and offers a detailed look at the social media footprint of the 2012 London Games, discussing how organizers, sponsors, media, and activists responded to the world's largest media event. In the end, Miah does not argue that physical activity will cease to be central to sports, or that digital corporeality will replace the nondigital version. Rather, he provides a road map for how sports will become mixed-reality experiences and abandon the duality of physical and digital.